Revitalizing Islamic Historical Narratives through Audiovisual Media as an Innovation in Islamic Cultural History (SKI) Learning at Madrasah Ibtidaiyah - Sri Ningsih; Elin Viana; Inshita Arisna Putri; Fatimatuz Zahro; Yasmin Suha Karimah; Siti Tawinatul Riskiyana; Salwa Kamilah Mufidah; Dian Rif’iyati (The Future of Education Journal, 2026)
Learning Islamic Cultural History (ISHC) in Islamic Elementary Schools (Madrasah Ibtidaiyah) often faces various challenges, such as low student interest, monotonous learning methods, and difficulties in bringing abstract historical narratives to life. This study aims to assess the effectiveness of using audiovisual media as a learning innovation in bringing Islamic historical narratives to life and developing relevant and sustainable learning models. The study used a qualitative approach with a literature study (library research) that reviewed 18 scientific sources in the form of journal articles and academic books published between 2018 and 2025. Data collection was carried out through documentation, while data analysis used descriptive qualitative analysis with the stages of data reduction, data presentation, and conclusion drawing. Source triangulation was used to ensure data validity. The results of the study indicate that audiovisual media have significant potential in improving student understanding, motivation, and engagement in ISHC learning. Media such as animated videos, educational films, and narrative podcasts are able to present material in a concrete, engaging, and contextual manner, making it easier for students to understand Islamic historical events and internalize Islamic character values. In addition, the audiovisual-based storytelling approach is effective in building a more meaningful learning experience. However, its implementation still faces challenges such as limited facilities, low teacher digital literacy, and limited access to learning resources. Therefore, ongoing support in the form of improving teacher competency and providing adequate facilities is needed to ensure optimal integration of audiovisual media into SKI learning.